Latent optical nonclassicality of conditionally prepared states - Kovtoniuk, Vadym; Klimov, Andrei; Semenov, Andrii (Physical Review A, 2025)
The lack of information obtained from informationally incomplete quantum measurements can prevent the detection of quantum resources, such as optical nonclassicality. We develop a technique that overcomes this limitation for single-mode quantum states conditionally prepared through measurements on another mode of a two-mode state. This task is performed by testing steering of latent nonclassicality—a class of correlations beyond quantum entanglement and quantum discord—for which we introduce a rigorous description.